Instructors’ perceptions on the use of formative assessment and feedback for learning during the COVID-19 pandemic: Another look inside the black box (Journal of Applied Learning and Teaching, 2025)
The COVID-19 pandemic has caused a significant disruption in the learning and teaching practices within the higher education sector in Singapore. This study examines the effectiveness of formative assessment, feedback, and peer assessment on undergraduate and postgraduate students’ learning outcomes during the pandemic. This study was conducted using a qualitative approach, where semi-structured interviews were conducted with 16 part-time and full-time instructors employed by an American university with an Asia campus in Singapore. The findings revealed that instructors generally felt that feedback improves students’ learning, motivation, and engagement. However, many instructors provided a mixed response concerning the benefits and limitations of using peer assessment. For benefits, instructors agreed that peer assessment offers an opportunity for students to acquire essential skills such as critical thinking, communication, teamwork, time management, and collaborative learning. These skills are important learning goals for their future academic and professional careers. In contrast, several instructors observed that peer assessment may not be beneficial when students lack motivation or skills to perform it, and it is time-consuming for students to complete and instructors to review. These findings have more far-reaching implications for instructors and the university in the post-pandemic era.